Gut-Brain Axis: Possible Role of Gut Microbiota in Perioperative Neurocognitive Disorders - Wang, Xiao-qing; Li, He; Li, Xiang-nan; Yuan, Cong-hu; Zhao, Hang (Frontiers in Aging Neuroscience, 2021)
Aging is becoming a severe social phenomenon globally, and the improvements in health care and increased health awareness among the elderly have led to a dramatic increase in the number of surgical procedures. Because of the degenerative changes in the brain structure and function in the elderly, the incidence of perioperative neurocognitive disorders (PND) is much higher in elderly patients than in young people following anesthesia/surgery. PND is attracting more and more attention, though the exact mechanisms remain unknown. A growing body of evidence has shown that the gut microbiota is likely involved. Recent studies have indicated that the gut microbiota may affect postoperative cognitive function via the gut-brain axis. Nonetheless, understanding of the mechanistic associations between the gut microbiota and the brain during PND progression remains very limited. In this review, we begin by providing an overview of the latest progress concerning the gut-brain axis and PND, and then we summarize the influence of perioperative factors on the gut microbiota. Next, we review the literature on the relationship between gut microbiota and PND and discuss how gut microbiota affects cognitive function during the perioperative period. Finally, we explore effective early interventions for PND to provide new ideas for related clinical research.